Opportunities and Challenges in the Art and Design Industry Under the Environment of Artificial Intelligence - Zhou, Xin (Journal of Theory and Practice of Management Science, 2025)
With the rapid development of computer technology, artificial intelligence (AI) has been widely applied in the field of art and design. This article briefly summarizes the definition and development process of AI, and combines the analysis of cutting-edge research and application cases of AI in the art and design industry to make prospects for the future development of the industry and designers, thereby promoting researchers in related fields to explore industry application models and development directions.